Disease-Based Prognostication: Neuro-Oncology - Waite, Kristin A.; Cioffi, Gino; Malkin, Mark G.; Barnholtz-Sloan, Jill S. (Seminars in Neurology, 2023)
Primary malignant and non-malignant brain and other central nervous system (CNS) tumors, while relatively rare, are a disproportionate source of morbidity and mortality. Here we provide a brief overview of approaches to modeling important clinical outcomes, such as overall survival, that are critical for clinical care. Because there are a large number of histologically distinct types of primary malignant and non-malignant brain and other CNS tumors, this chapter will provide an overview of prognostication considerations on the most common primary non-malignant brain tumor, meningioma, and the most common primary malignant brain tumor, glioblastoma. In addition, information on nomograms and how they can be used as individualized prognostication tools by clinicians to counsel patients and their families regarding treatment, follow-up, and prognosis is described. The current state of nomograms for meningiomas and glioblastomas are also provided.
Keywords: meningioma; glioblastoma; clinical outcomes; nomogram; biomarkers